Raring to go? A cross-sectional survey of student paramedics on how well they perceive their UK pre-registration course to be preparing them to manage suspected seizures - Adam J. Noble; Carolyn Lees; Kay Hughes; Lucy Almond; Hesham Ibrahim; Cerys Broadbent; Pete Dixon; Anthony G. Marson (BMC Emergency Medicine, 2023)
Abstract Background Paramedics convey a high proportion of seizure patients with no clinical need to emergency departments (EDs). In a landmark study, only 27% of UK paramedics reported being “Very…”/ “Extremely confident” making seizure conveyance decisions. Improved pre-registration education on seizures for paramedics is proposed. Clarity is needed on its potential given recent changes to how UK paramedics train (namely, degree, rather than brief vocational course). This study sought to describe UK student paramedics’ perceived readiness to manage seizures and educational needs; compare this to what they report for other presentations; and, explore subgroup differences. Methods Six hundred thirty-eight students, in year 2 or beyond of their pre-registration programme completed a cross-sectional survey. They rated perceived confidence, knowledge, ability to care for, and educational needs for seizures, breathing problems and, headache. Primary measure was conveyance decision confidence. Results For seizures, 45.3% (95% CI 41.4–49.2) said they were “Very…”/“Extremely confident” to make conveyance decisions. This was similar to breathing problems, but higher than for headache (25.9%, 95% CI 22.6–29.5). Two hundred and thirty-nine participants (37.9%, 95% CI 34.1–41.8) said more seizure education was required – lower than for headache, but higher than for breathing problems. Subgroup differences included students on university-based programmes reporting more confidence for conveyance decisions than those completing degree level apprenticeships. Conclusions Student paramedics report relatively high perceived readiness for managing seizures. Magnitude of benefit from enhancements to pre-registration education may be more limited than anticipated. Additional factors need attention if a sizeable reduction to unnecessary conveyances for seizures is to happen.